Menanamkan Pengetahuan Keagamaan pada Anak Melalui Pembiasaan Membaca Asmaul Husna di TK Masyithoh II Sanansari - Muhammad Choirul Anam; Wahidin; Nurul Fauziah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The provision of the habit of reading Asmaul Husna aims to instil religious values in children from an early age. The type of research used is field research with descriptive qualitative methods. To obtain credible research, the researchers used triangulation techniques and used interviews, observations and documentation in data collection. The results of this study are educators teach children to read Asmaul Husna by using a screen or projector in front of them, and then the educator points to the letters one by one. Besides that, the educator also teaches children to write Asmaul Husna, and then the results are displayed in a temple in front of the class as a form of reward for the children.